2005
DOI: 10.1111/j.1365-2524.2005.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowing the diagnosis and counselling the relatives of a person with dementia: the perspective of home nurses and home care workers in Belgium

Abstract: Home nurses and home care workers share the care for a person with dementia with family caregivers, and are confronted with their needs for medical and service-related information, for advice on how to cope with the behaviour changes, and for emotional support. The first objective of the present study was to describe some of the conditions for effective counselling, such as the perception that knowing the diagnosis has positive consequences for the formal caregivers. A second objective was to describe the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Only a few studies focused on specific types of clients (e.g. people with dementia) [9,31,32,68]. Finally, many studies had a limited geographical scope and explored a single municipality or area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies focused on specific types of clients (e.g. people with dementia) [9,31,32,68]. Finally, many studies had a limited geographical scope and explored a single municipality or area.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies provided information on more than one of the four domains distinguished ('policy & regulation', 'financing', 'organisation & service delivery' and 'clients & informal carers') [8,9,11-16,18,19,21,23,25,26,28-31,34,35,37-41,44,47-51,55,57,58,60-62,64,67,69,71,76-81]; close to one-third focused on only one of them. For most countries information was available for each of the four domains, but the amount of information per domain differed considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Care managers also had the highest level of self confidence among community health nurses. These results provide indirect evidence that knowledge of social resources and self confidence are positively correlated to the ability to provide dementia care (Kaduszkiewicz et al, 2008;Roelands et al, 2005). Home health care nurses were the ones that most often received and handled a referral for treatment and provided knowledge about dementia to caregivers.…”
Section: Variablesmentioning
confidence: 86%
“…among the various roles of community health nurses (Manthorpe et al, 2003;Roelands et al, 2005;Trickey et al, 2000). These studies concluded that attitude and confidence toward dementia care and the role of professionals have a pivotal impact on how dementia care is practiced.…”
Section: Introductionmentioning
confidence: 99%
“…Papers included studies from Israel (Ben-Arie & Lecovich, 2014), Japan (Igarashi et al, 2015), United States (US) Riesenbeck et al 2015;Butler, 2009), Canada (Morgan et al 2016), Belgium (Roelands et al 2005) and the UK (Dawson et al 2015;Devlin & McIlfatrick, 2009;Ryan et al 2004;Herber & Johnston, 2013) …”
Section: Data Synthesismentioning
confidence: 99%